The three little superpigs : once upon a time - Evans, Claire (Illustrator) (New York : Scholastic Press, 2019)
When they arrive in Fairyland to settle down and build their own houses, everyone they meet warns the three little superpigs about the Big Bad Wolf, but only one of them pays much attention--and when the Wolf comes looking for a pork dinner, it is his brick house that saves his foolish brothers and earns them all the status of superheroes in Fairyland (which is what they have always dreamed of being).
"The Three Little Superpigs: Once Upon a Time was originally published in Great Britain by Fourth Wall Publishing in 2017 under the title The Three Little Superpigs: The Origin"--Copyright page.
Accelerated Reader AR
Keywords: Three little pigs -- Adaptations; Swine -- Juvenile fiction; Brothers -- Juvenile fiction; Wolves -- Juvenile fiction; Superheroes -- Juvenile fiction; Fairy tales; Humorous stories; Humorous fiction